CLINICAL REZULTS OF IMPLANTATION TREATMENT IN COMBINATION WITH HORIZONTAL ALVEOLAR RIDGE AUGMENTATION IN MANDIBLE - Călin Dorelia; Rusu Anca; Mitrea Mihaela (Romanian Society of Oral Rehabilitation, 2014)
Oral rehabilitation of partially edentulous patients with dental implants is practiced more frequently. An ideal bone volume is essential for the proper placement of the implant, bone loss after tooth extraction or due to periodontal disease can complicate the placement of endosseous implants due to insufficient height or width of residual bone. This can be overcomed by procedures of ridge augmentation that can restore the lost bone volume. The purpose of this study is to evaluate whether bone substitutes together with autogenous bone can successfully augment very resorbed alveolar ridges. The horizontal augmentation was performed at mandibular alveolar ridge in a total number of 21 patients. There were obtained increases in bone volume in a range between 3 and 7 mm. The obtained bone volume as a result of the regeneration was adequately in order to place implants in an ideal position from a prosthetic point of view. Bone regeneration using a combination of autogenous bone and bovine bone is a predictable procedure in the mandible, and could thus augment the bone volume and being possible the insertion of implants even in case of very resorbed ridge.